The design of the push-pull voltage regulator with class AB output stage with an embedded voltage reference - Gao, Liuyue (Nanyang Technological University, 2024)
This paper discusses the design of a Push-Pull voltage regulator with Class AB output stage voltage regulator and embedded voltage reference, aiming at enhancing power efficiency and stability in various electronic applications. Unlike Low Dropout regulators limited by low current consumption and designed for specific CMOS technology nodes, the Push-Pull configuration, complemented by a Class AB output stage, offers a broader range of load handling capabilities and improved efficiency, particularly in systems where load conditions vary widely.